All-Inorganic Perovskite Solar Cells: Energetics, Key Challenges, and Strategies toward Commercialization - Faheem, M. Bilal; Khan, Bilawal; Feng, Chao; Farooq, M. Umar; Raziq, Fazal; Xiao, Yequan; Li, Yanbo (ACS energy letters, 2020)
Since the first report of all-inorganic perovskite solar cells (PSCs) in 2014, more than 200 research articles have been published on this topic, reporting the enhancement in the stabilized power conversion efficiency (PCE) up to 18.4%. All-inorganic PSCs have become one of the most astonishing research domains in the field of perovskite-based photovoltaics. In this Review, significant improvements in all-inorganic PSCs are analytically reviewed, with some insight into the kinetics of intrinsic phase, light, and thermal stability of all-inorganic perovskites. Theoretical calculations specify that there is still a large capacity for further enhancement of device parameters. The critical challenges and the possible elucidations concerning improving the performance of all-inorganic PSCs are also discussed. Our focus is on the assessment of all-inorganic perovskite materials’ properties and the recapitulation of the latest approaches of improving the PCE of corresponding devices in order to introduce new horizons toward commercialization.